Climate change projections and impacts on raw water quality in the Paraíba do Sul River basin, Southeast Brazil - de Moura Rahmani, Diovana; Satolo , Luiz Fernando; Acioli Canamary , Erica; Tomasella, Javier (Sustainability in Debate, 2026)
This study aims to assess recent trends in water quality indicators in the Paraíba do Sul River Basin in the state of São Paulo and to analyse the influence of climate change on these parameters. A comparative analysis between future projections and a historical reference scenario reveals that climate variability plays a significant role in water quality. Additionally, the findings indicate a decline in water availability, particularly under high emission scenarios, underscoring the urgency of mitigation and adaptation measures to ensure water security in the region.